PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, DAN CURRENT RATIO TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BEI TAHUN 2011-2013 - Diah Rosiana Wati, 11.05.51.0087; Irsad, Moch. (Students Journal of Economic and Management, 2015)
The purpose of the research is to examine the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), and Current Ratio (CR) on Dividend Payout Ratio (DPR). This reseach is focus on manufacturing company at Indonesian Stock Exchange during the period 2011, 2012, and 2013. In this study, researchers used purposive sampling and obtain a sample of 57 sample companies. The analysis data use multiple regression model. The result show that Debt to Equity Ratio (DER) has negative and significans effect, Return on Assets (ROA) has positive and significans effect, and than Current Ratio (CR) has positve and no significans effect. The Adjusted R Square is 0,526. It means that 5,26% variation of Dividend Payout Ratio influenced by the Debt to Equity Ratio (DER), Return on Assets (ROA), and Current Ratio (CR), while the rest of 47,4% influenced by other factors which are not included in the model. Keyword: DER, ROA, Current Ratio, and Dividend Payout Ratio